2011
DOI: 10.1007/s12247-011-9103-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pharmaceutical Tablet Coating Uniformity by Laser-Induced Breakdown Spectroscopy (LIBS)

Abstract: A laser-induced breakdown spectroscopy-based analytical methodology is developed to study tablet coating variability in pharmaceutical tablets. The method quantifies the amount of coating on a tablet by assigning an average coating thickness score to it. When tested using samples with different amounts of coating, the coating thickness scores showed direct correlation to the weight gain of the tablet, hence validating the analytical method. The relative significance of the processing parameters and the compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
(34 reference statements)
1
11
0
6
Order By: Relevance
“…It has been shown in previous studies that the tablet-totablet coating variability is inversely proportional to the square root of weight gain (28) or coating time (3,6,30). In this study, the evolution of the RSD as a function of square root of weight gain for all lots is displayed in Fig.…”
Section: Effect Of Coating Weight Gainmentioning
confidence: 72%
See 3 more Smart Citations
“…It has been shown in previous studies that the tablet-totablet coating variability is inversely proportional to the square root of weight gain (28) or coating time (3,6,30). In this study, the evolution of the RSD as a function of square root of weight gain for all lots is displayed in Fig.…”
Section: Effect Of Coating Weight Gainmentioning
confidence: 72%
“…Another sample set, referred to as set M1, was used to develop the analytical method. Complete ANOVA and variance calculations for the method development study are not presented here, but can be found in Dubey et al (28). Set M1 consisted of 100 tablets sampled from five production batches with 20 tablets per batch.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A változatosság a "batch"-ek között, melyeket azonos körülmények között állítottak elő, nem volt jelentős [92].…”
Section: Gyógyszeripari Alkalmazásokunclassified